Fluorescent chemodosimeter for quantification of cystathionine-γ-synthase activity in plant extracts and imaging of endogenous biothiols. Issue 65 (30th July 2018) - Agarwalla, Hridesh; Anila, H. A.; Ali, Firoj; Pradhan, Swaraj Rashmi; Ganguly, Bishwajit; Pramanik, Sumit Kumar; Das, Amitava
Abstract : Chemodosimetric reagent for quantification of cystathionine-γ-synthase and mapping endogenous biothiols with luminescence ON response. Abstract : A new reagent for quantification of CgS in plant extracts using a generalized methodology suitable for recognition of homocysteine (Hcy) with luminescence ON response.